Integration of phospholipid-drug complex into self-nanoemulsifying drug delivery system to facilitate oral delivery of paclitaxel - Dawei Ding; Bingjun Sun; Weiping Cui; Qin Chen; Xuanbo Zhang; Haotian Zhang; Zhonggui He; Jin Sun; Cong Luo (Elsevier, 2019)
Self-nanoemulsifying drug delivery system (SNEDDS) has emerged as a promising platform to improve oral absorption of drugs with poor solubility and low permeability. However, large polarity molecules with insufficient lipid solubility, such as paclitaxel (PTX), would suffer from inferior formulation of SNEDDS due to poor compatibility. Herein, phospholipid-drug complex (PLDC) and SNEDDS were integrated into one system to facilitate oral delivery of PTX. First, PTX was formulated into PLDC in response to its inferior physicochemical properties. Then, the prepared PLDC was further formulated into SNEDDS by integrating these two drug delivery technologies into one system (PLDC-SNEDDS). After PLDC-SNEDDS dispersed in aqueous medium, nanoemulsion was formed immediately with an average particle size of ∼30 nm. Furthermore, the nanomulsion of PLDC-SNEDDS showed good colloidal stability in both HCl solution (0.1 mol/l, pH 1.0) and phosphate buffer solution (PBS, pH 6.8). In vivo, PTX-PLDC-SNEDDS showed distinct advantages in terms of oral absorption efficiency, with a 3.42-fold and 2.13-fold higher bioavailability than PTX-PLDC and PTX solution, respectively. Our results suggest that the integration of PLDC into SNEDDS could be utilized to facilitate the oral delivery of hydrophobic drugs with large polarity. Keywords: PTX, PLDC, SNEDDS, PLDC-SNEDDS, Oral delivery